Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11060-010-0279-5
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with hematopoietic stem cell transplantation for the treatment of primary central nervous system lymphoma

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare B-cell lymphoid neoplasm for which current regimens utilizing standard-dose chemotherapy and/or radiation therapy lead to high relapse rates and/or unacceptable neurologic sequelae. High-dose chemotherapy followed by hematopoietic stem cell transplantation may overcome limitations of current treatment schemas. A search was performed of all English-language literature (1968 to June 2009) within the MEDLINE, EMBASE and Cochrane Library databases to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
5
0
4
Order By: Relevance
“…Indeed, a recent review of clinical experience with PCNSL concluded that high-dose chemotherapy ± whole-brain radiotherapy followed by autologous HSCT holds promise to improve patient outcomes. 2 Although this latest review of PCNSL is thought-provoking, we find discrepancies that may confound the authors' conclusions.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Indeed, a recent review of clinical experience with PCNSL concluded that high-dose chemotherapy ± whole-brain radiotherapy followed by autologous HSCT holds promise to improve patient outcomes. 2 Although this latest review of PCNSL is thought-provoking, we find discrepancies that may confound the authors' conclusions.…”
mentioning
confidence: 81%
“…2 Bearing in mind not only the variations in chemotherapy regimens, but also the variations of survival seen in these studies, we are surprised to find the authors' conclusion of superiority with 'thiotepa/busulfan based conditioning' and recommendation of this strategy as a 'suggested treatment approach in patients with PCNSL'. 1 Although these two agents may have a role in conditioning for autologous HSCT to treat newly-diagnosed PCNSL, the scarcity of data makes their role ill-defined.…”
mentioning
confidence: 93%
See 3 more Smart Citations